1999
DOI: 10.1034/j.1399-3003.1999.14a09.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in elderly subjects with a diagnostic label of asthma from general practice registers

Abstract: The aim of this study was to assess health-related quality of life (QoL) in elderly subjects with a diagnostic label of asthma from a general practice population, and to determine the main contributory factors.Sixty people aged $70 yrs with a primary care diagnostic label of asthma, and 43 control subjects were recruited. Assessment of bronchodilator response, and oral steroid trials were conducted where possible. The main outcome measures were QoL scores for the Short Form (SF)-36 and the St George's Respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 30 publications
3
28
0
3
Order By: Relevance
“…An experimental study inducing stress under laboratory conditions in adults with asthma revealed a rapid and significant increase in respiratory symptoms immediately following exposure to stressful stimuli eliciting negative emotions [22]. Similarly, psychological status, i.e., depression, appears to be an important predictor of reduced QoL in both young and elderly asthmatics [23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 97%
“…An experimental study inducing stress under laboratory conditions in adults with asthma revealed a rapid and significant increase in respiratory symptoms immediately following exposure to stressful stimuli eliciting negative emotions [22]. Similarly, psychological status, i.e., depression, appears to be an important predictor of reduced QoL in both young and elderly asthmatics [23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed either younger [12,13] or elderly [7] patients with asthma suffered from psychological depression. Adams et al [14] documented that psychological distress and decreased feelings are common in asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto à relevância do factor idade, esta tem sido salientada por outros autores. Nos indivíduos com asma brônquica de faixas etárias mais avançadas, a asma parece contribuir para a diminuição da sua qualidade de vida (Dyer, Hill, Stockely & Sinclair, 1999). Verifica-se a ocorrência de um conjunto de complicações físicas e psicológicas associadas (e.g., maior sintomatologia depressiva, maiores limitações das actividades diárias e um estado de saúde pobre) que dificultam o processo de gestão da doença (Enright, Mclelland, Newman, Gottlieb & Lebowitz, 1999).…”
Section: Discussionunclassified